Development of Tailored Teaching Model for Beginning Piano Level Among Visually Impaired Students - Chen, Chun; Kaenampornpan, Pornpan; Sapaso, Pongpitthaya (Journal of Ecohumanism, 2024)
Music education for visually impaired individuals faces significant challenges due to traditional methods relying heavily on visual cues. This study addresses this gap by developing a tailored teaching model for beginning piano instruction among visually impaired students. Through a multi-phase methodology, including pilot teaching, expert interviews, and formal teaching sessions, the study integrates innovative pedagogical strategies and adaptive technologies to create an inclusive learning environment. The pilot teaching phase was conducted at a specialized school for the blind and deaf in Jiangsu, China, involving six visually impaired students with varying levels of piano learning experience. Expert interviews were conducted with three individuals with expertise in music education for visually impaired individuals. The formal teaching phase comprised six new visually impaired students and spanned three months, with assessments conducted after the 5th and 10th lessons to evaluate learning progress. Results demonstrate the effectiveness of the tailored teaching model in fostering meaningful musical experiences and promoting musical proficiency among visually impaired students. Suggestions for further research and implementation of tailored teaching models are provided to enhance access to music education for visually impaired individuals.